1997
DOI: 10.1111/j.1365-2133.1997.tb03786.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with the severity scoring of atopic dermatitis in a population of German pre-school children

Abstract: Severity scoring of atopic dermatitis (SCORAD) was introduced as a standard tool but has not been used in a population-based epidemiological study; the objective of the present study was to determine the practicability of this instrument in this setting. We assessed the distribution of the severity of atopic eczema in the community and investigated differences between east and west Germany. A factor analysis was then carried out to characterize the variables of this scoring system and to analyse possible relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 6 publications
1
27
0
3
Order By: Relevance
“…In accord with previous studies on the SCORAD index and AD prevalence in children, we also found an index in our subcohort categorized as mild at baseline [32,33]. Despite this low SCORAD index, children and infants registered a positive and a significant benefit of the skin care regimes in our trial.…”
Section: Discussionsupporting
confidence: 91%
“…In accord with previous studies on the SCORAD index and AD prevalence in children, we also found an index in our subcohort categorized as mild at baseline [32,33]. Despite this low SCORAD index, children and infants registered a positive and a significant benefit of the skin care regimes in our trial.…”
Section: Discussionsupporting
confidence: 91%
“…18 Data from other epidemiological studies have equally shown that most AD cases are characterized as mild and moderate and only 1% to 2% as severe. [26][27][28][29][30] Even if the present cohort is at high risk for development of AD, the severity of symptoms should not necessarily be expected to be increased compared with children with AD from a nonrisk population.…”
Section: Commentmentioning
confidence: 99%
“…For full study names see indicated references. ing SCORAD in an epidemiological study 37 and in a multinational randomized trial. 38 In the latter study, reliability was tested using 3 members of the European Task Force and 98 observers using selected photographs of patients.…”
Section: The Scorad Indexmentioning
confidence: 99%